PENERAPAN TEKNIK NUNO FELTING PADA WOL DOMBA WONOSOBO UNTUK SYAL - Celine Lahji (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
The background of the creation of this work is the introduction of the nuno felting technique to farmers and craftsmen in the village of Bomerto, Wonosobo to utilize the wool of the Wonosobo Sheep which is exported abroad. This happens because Indonesia has not been able to process wool into a work that has high value and is useful for society. From these problems, it is possible to create new works that will add value to the renewal to encourage the development of textile technology and as another alternative in processing Wonosobo Sheep's wool with the nuno felting technique. The problem in this design is how to apply the nuno felting technique to Wonosobo Sheep wool and organza silk which can be realized in the form of a scarf with geometric motifs. In solving this design problem strategy using Gustami's theory, namely by way of exploration, design, and embodiment by considering aspects of observation, visual studies, product comparisons and the trial phase. The result of this design is a scarf product with the nuno felting technique in the form of 7 designs and 2 scarf products measuring 140 x 50cm. It is hoped that the Nuno felting technique can create functional products and look to the government to advance the creative economy in society.